Factores relacionados con el incumplimiento del esquema de vacunación en lactantes de 6-12 meses atendidos en el Centro de Salud Urbano de Quevedo. octubre 2018- abril 2019 - Gutierrez Zamora, Joselyne Elena (2019)
Vaccines worldwide have become the product of greatest benefit to the community, failure to comply with the vaccination scheme generates very low and insufficient coverages in our country and in our province, and it also brings complications for the child. The purpose of this work is to determine the factors related to the noncompliance of the vaccination scheme in infants of 6-12 months attended in the urban health center of Quevedo, in the period of October 2018 - April 2019, for which a quantitative approach was used, descriptive and transversal. The study was conducted in 60 mothers of children under 1 years of age, who were given a survey in order to know their criteria and perspectives concerning vaccination. The data obtained were processed statistically, with the result that 65% of mothers between 21 and 35 years of age, in free union, 35% are mothers who have studied secondary school, do not have stable work, finally 65% of mothers They refer not to vaccinate their children because of ignorance of the importance of the vaccine within the first 5 years of life and for a bit of carelessness, 56% of mothers have difficulty mobilizing that some expect the EAIS arrive at home, which means that the mothers of a family there is a range that are adolescents that this gives us a reflection of a little irresponsibility on the part of the mothers. Factors affect knowledge, more than personal factors.